Glucose Control: non-insulin therapies* - The Society for Endocrinology Metabolism and Diabetes of South Africa (South African Family Practice)
This chapter summarises information for each of the non-insulin drug classes that are used for blood glucose control. Each summary is accompanied by a table of recommendations to guide the clinical use of these medications. For the sake of completeness, and for those that are interested, we have included a more detailed review of each drug as an appendix to each summary. These can be found in the Appendix section of the guidelines. The treatment recommendations for each drug have been incorporated into the treatment algorithm in Chapter 11. The following abbreviations are used in this chapter: DPP-4: dipeptidyl peptidase-4 GLP-1: glucagon-like peptide-1 SGLT2- sodium-glucose linked transporter-2